Effects of cold storage on the quality of Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) reared on artificial medium. Issue 5 (4th December 2018) - Lü, Xin; Han, Shichou; Li, Jun; Liu, Jisheng; Li, Zhigang
Abstract: BACKGROUND: Trichogramma dendrolimi Matsumura is an important egg parasitoid that can be used in the biological control of lepidopteran pests. The effects of storage temperature, developmental stage and storage duration on development and survival were investigated to determine the optimum storage conditions for rearing T. dendrolimi in vitro . RESULTS: The three investigated factors significantly impacted all the biological parameters except for parental G1 and offspring G2 sex ratios. The responses of in vitro reared T. dendrolimi to low temperatures differed depending on developmental stage and storage duration. Comparison of life table parameters under different storage treatments with the control group indicated that storing prepupae at 13 °C for 2, 3 or 4 weeks positively impacted the growth capacity of the parasitoid. CONCLUSION: In vitro reared T . dendrolimi can be reared following cold storage. The quality of the parasitoid was strongly affected by cold storage, likely due to the negative effects of storage on the artificial medium. Storage of the prepupal stage at 13 °C for 4 weeks is optimum for in vitro reared T. dendrolimi . Trichogramma reared in vitro were able to parasitize natural eggs after storage and, thus, have potential for use as biological control agents in the field. © 2018 Society of Chemical Industry Abstract : This study investigated the effects of cold storage and optimum storage conditions of in vitro reared Trichogramma dendrolimi, an economically important biological control agent.